1992
DOI: 10.1177/036354659202000306
|View full text |Cite
|
Sign up to set email alerts
|

A profile of the musculoskeletal characteristics of elite professional ballet dancers

Abstract: Twenty-eight principal dancers and soloists from America's two most famous ballet companies were examined for anthropometric measurements, including flexibility, muscle strength, and joint range of motion. Both male and female dancers were flexible, but not hypermobile, and did not differ significantly from each other. Marked differences were found between the range of motion of the hip and ankle in the dancers and the norms for the general population. The increased external rotation of the hip in women was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
234
2
19

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(265 citation statements)
references
References 20 publications
10
234
2
19
Order By: Relevance
“…35,46,50,51,63,64 Many authors suggest that there are measurable intrinsic characteristics that contribute to dance injuries, 8,18,26,34,61,66 such as imbalances in strength and flexibility, insufficient or excessive joint range of motion, or poor postural alignment. 8,24,26,34,66 While these may be intuitive assumptions, very few studies have been conducted to investigate the relationships between measurement of intrinsic characteristics and dance injuries.…”
Section: Rate Of Injuriesmentioning
confidence: 99%
“…35,46,50,51,63,64 Many authors suggest that there are measurable intrinsic characteristics that contribute to dance injuries, 8,18,26,34,61,66 such as imbalances in strength and flexibility, insufficient or excessive joint range of motion, or poor postural alignment. 8,24,26,34,66 While these may be intuitive assumptions, very few studies have been conducted to investigate the relationships between measurement of intrinsic characteristics and dance injuries.…”
Section: Rate Of Injuriesmentioning
confidence: 99%
“…Depending on the type of dance and its duration, the effort exerted when dancing requires not only an efficient cardiorespiratory system (both aerobic and anaerobic pathways) but also significant muscle strength and power [1,2]. Previously published data on the levels of physical fitness of dancers and the physiological response during dancing focused mainly on modern and ballroom dancing, ballet, and aerobic dance workouts [3][4][5][6][7][8][9][10][11][12][13]. These studies found that the aerobic fitness level of dancers can be considered as average and characteristic of individuals practicing non-endurance sports [3,5,9,13].…”
Section: Introductionmentioning
confidence: 99%
“…Foi encontrado que 70% das bailarinas apresentaram joelhos valgos, assim como as bailarinas estudadas por Prati e Prati (2006) Hamilton et al (1992), isso pode dever-se à grande mobilidade articular, pois os dançarinos devem possuir um elevado grau de dorsiflexão de tornozelo para adotar a posição do plié e suportar as aterrissagens de saltos. Problemas no tornozelo e no pé são comuns na população de dançarinos, pois o esforço para conseguir uma rotação externa de membros inferiores resulta em alterações na biomecânica das bailarinas, podendo levar ao aparecimento de lesões durante a execução dos movimentos do balé clássico (SCHON;WEINFELD, 1996).…”
Section: Discussionunclassified